INFINITESIMAL BENDING OF CURVES - Velimirović, Ljubica S. (Matematichki Bilten, 2001)
In this paper we consider infinitesimal bending of curves in \(R^3\). The field of infinitesimal bending and deformed curve is given. Infinitesimal bending of circle is investigated. Variation of the torsion and curvature for a circle under infinitesimal bending is considered. Infinitesimal bending that plane curve remains in the plane is given. Infinitesimal bending is studied not only analytically, but also by drawing curves.